UJI VALIDITAS DAN RELIABILITAS BEBERAPA ALAT SWA-MONITOR KOMERSIAL UNTUK PEMERIKSAAN KADAR GLUKOSA DARAH DAN STUDI PENGARUH FAKTOR LOKASI PENGAMBILAN SAMPEL TERHADAP HASIL PENGUKURAN - Oesricha Pakki, Tasya
Blood glucose monitoring is the most routine general checkup that been done independently by society regarding the incidence and prevalence of diabetes mellitus, particularly type 2. Recently, there are many self-monitoring devices for blood glucose, known as glucometer which globally market. This study aimed to determine the validity of glucometers from several brands compared to the standard method spectrophotometer which is done by clinical laboratory, determine the reliability of the glucometers, examine the impact of the location of sample collection to the result of the blood glucose measurement and also developed the information and appropriate recommendation of glucometer usage. This study was done to five subjects to compare the measurement of blood glucose using the glucometers and spectrophotometer as a standard method. Within the same time, sample collection is done on vein and capillary blood. On this study, blood samples also been taken from five subjects for twelve times in a month on the right and left hand to examine the reliability and to see any effect from sampling location. The result is statistically analyzed using the paired t-test and Cronbach's alpha. The result showed that there are no significant differences between the measurement of blood glucose using glucometers and spectrophotometer with the p-value in brand ET, AC, and NES are 0.0934, 0.0766, 0.6926 (>0.05) respectively. Next, the result of blood glucose measurement between left and right hand is significantly different with P-value in brand ET, AC, and NES are P<0.0001 (<0.05) and established similar repeatability of results on both hands. On reliability test, the Chronbach’s alpha value for glucometer brand ET, AC, and NES on daytime measurement are 0.6964, 0.7208, and 0.5459 respectively. Meanwhile, on night-time, the alpha value is resulted in the yield 0.7814, 0.7426, and 0.7703. This study leading to the conclusion that the glucometers are valid compared to the standard method and the reliability of the glucometer is better at night-time measurement while the result of right hand blood glucose is higher than left hand meaning that the location of sample collection affects the results of the measurement.